Conflict and Shifting Boundaries in the Gig Economy : an Interdisciplinary Analysis - Yerby, Elaine (Changing context of managing people., 2020)
Using an interdisciplinary approach, this book draws on legal, HRM, occupational psychology and economic perspectives to innovatively explore the conflicts and blurring boundaries affecting the Gig Economy in terms of the worker, employee identity, status and relationships, and team and career management.